Nickel(II) metal-organic frameworks with N,N’-di(4-pyridyl)-1,4,5,8-naphthalenetetracarboxydiimide ligands: influence of secondary building unit geometry on dimensionality and framework dimensions - Pfeiffer, Constance R.; Biggins, Naomi H.; Lewis, William; Champness, Neil R. (Royal Society of Chemistry, 2017)
When Ni(NO3)2∙6H2O and N,N’-di(4-pyridyl)-1,4,5,8-naphthalenetetracarboxydiimide (DPNDI) are reacted, a one-dimensional coordination polymer (1) is formed. However, reaction with either terephthalic acid (2) or 2,6-naphthalenedicarboxylic acid (3) affords two-dimensional, pillared metal-organic frameworks. 2 and 3 containing rectangular voids of different dimensions which are dictated by the carboxylate ligand and the arrangement of the [M(k2-O2NO)]2(μ2-O2CR)2] secondary building unit (SBU) that forms the nodes of the framework. The role of SBU geometry, intermolecular face-to-face π–π and lone pair–π interactions involving the DPNDI ligands are discussed.